The First Advisory Group Meeting (AGM) in Open and Distance Education - Georgios Giannoukos; Ioannis Stergiou; Vasilios Hioctour; Sotiria Kallianta (Journal of Education and Vocational Research, 2016)
The main reason for someone to participate in an Open and Distance Education program is either the acquisition of professional skills on a given object, or the development of his existing skills and consequently their improvement. By carrying out Advisory Group Meetings (AGM) on specific issues related to the trainees, a deepening of their theoretical background and the practical aspects of their training takes place, which they all seek. In this paper we present in a concise way the course of such a meeting according to the extent that it may have, in which the theory is being associated with practice.